Ex vivo normothermic perfusion of isolated segmental porcine bowel: a novel functional model of the small intestine. Issue 2 (11th April 2021) - Hamed, M O; Barlow, A D; Dolezalova, N; Khosla, S; Sagar, A; Gribble, F M; Davies, S; Murphy, M P; Hosgood, S A; Nicholson, M L; Saeb-Parsy, K
Abstract: Background: There is an unmet need for suitable ex vivo large animal models in experimental gastroenterology and intestinal transplantation. This study details a reliable and effective technique for ex vivo normothermic perfusion (EVNP) of segmental porcine small intestine. Methods: Segments of small intestine, 1.5–3.0 m in length, were retrieved from terminally anaesthetized pigs. After a period of cold ischaemia, EVNP was performed for 2 h at 37°C with a mean pressure of 80 mmHg using oxygenated autologous blood diluted with Ringer's solution. The duration of EVNP was extended to 4 h for a second set of experiments in which two segments of proximal to mid-ileum (1.5–3.0 m) were retrieved from each animal and reperfused with whole blood (control) or leucocyte-depleted blood to examine the impact of leucocyte depletion on reperfusion injury. Results: After a mean cold ischaemia time of 5 h and 20 min, EVNP was performed in an initial group of four pigs. In the second set of experiments, five pigs were used in each group. In all experiments bowel segments were well perfused and exhibited peristalsis during EVNP. Venous glucose levels significantly increased following luminal glucose stimulation (mean(s.e.m.) basal level 1.8(0.6) mmol/l versus peak 15.5(5.8) mmol/l; P < 0.001) and glucagon-like peptide 1 (GLP-1) levels increased in all experiments, demonstrating intact absorptive and secretory intestinal functions. There were no significant differences between control and leucocyte-depleted animals regarding blood flow, venous glucose, GLP-1 levels or histopathology at the end of 4 h of EVNP. Conclusions: This novel model is suitable for the investigation of gastrointestinal physiology, pathology and ischaemia reperfusion injury, along with evaluation of potential therapeutic interventions. Abstract : In this paper, we provide proof-of-concept evidence for the utility of Ex vivo normothermic perfusion of isolated segmental porcine bowel for the investigation of gastrointestinal physiology, pathology and ischaemia reperfusion injury, as well as for evaluation of potential therapeutic interventions An important investigative tool.